Environmental impacts generated by artisanal coal mining in Sanagorán, Huamachuco (SCIÉNDO INGENIUM, 2025)
The research aims to assess the environmental impacts resulting from coal extraction in artisanal mines located in Agopampa and Huacchac, within Sanagorán, Huamachuco. To achieve this, technical visits and field consultations were conducted with miners and local inhabitants. A methodology based on direct observation and data collection was applied, identifying environmental impacts on the abiotic components (water, soil, and air) and the biotic component (tree deforestation). The evaluation was based on environmental impact intensity criteria: high, medium, and low. A total of 21 environmental impacts were identified, with 40% classified as high intensity, 40% as medium intensity, and 20% as low intensity. One of the most alarming findings was the daily average consumption of 5424 kg of wood in the mines. Additionally, the increase in coal prices led to two main effects: a rise in solid waste production, heightening ecological concerns, and the commercialization of sterile materials, reducing their contaminating impact on the soil. In conclusion, the manual extraction of coal in the area has severe consequences for the ecosystem and public health, while also serving as a crucial economic source for many mining families.
Keywords: Environmental impact; artisanal mining; deforestation; soil and water pollution; coal mining